A stylistic journey through Basim Khandaqji’s novel, A Mask, the Colour of the Sky (2023) - Al-Alami, Suhair Eyad (Research Journal in Advanced Humanities, 2025)
The world of novels knows no boundaries for inspiration, recreation, and sophistication. The deeper we delve, the more intellectually enriched we become. And the more intellectually enriched we become, the greater our appreciation for masterpieces that transcend eras, generations, and cultures, enduring symbols of human creativity, authenticity, and sensibility throughout the years. Bearing this in mind, the current article aims to explore what novelists should achieve to win a globally recognised award, and examines the literary work A Mask, the Colour of the Sky, the winning novel of the Booker Prize for Fiction 2024, as a model for novelists and researchers to consider. To achieve the intended aims, the author of this paper set a ten-item questionnaire and conducted a textual analysis of the novel A Mask, the Colour of the Sky. Regarding the sample that responded to the questionnaire, it comprised forty-seven participants. The findings indicate that factors such as unique theme, intriguing plot, distinct setting, engaging content, compelling character, eloquent language, insightful dialogue, and narrative voice amongst others, may if impressively employed, enable a novelist to win a prestigious prize. The paper concludes with recommendations for novelists and researchers to consider.